AVALIAÇÃO DA ESTABILIDADE, DO PERFIL TOXICOLÓGICO EM RATOS WISTAR DE NANOCÁPSULAS CONTENDO MANGIFERINA - Carmo, Guilherme Machado do (2015)
This study aimed to verify the stability and toxicological profile in Wistar rats of nanocapsules containing mangiferin (NCM). Three batches of NCM were produced and stored at three different temperatures (room temperature, 2 to 8 °C and 40 °C). Particle size, zeta potential, drug content and pH were analyzed (at 0, 15, 30, 60 days) in order to evaluate the stability. Regarding the toxicological profile, a subchronic treatment of 24 days was applied. Two administration routes (orally and intraperitoneally) were evaluated. The animals were divided into 5 groups (n=8). After the period of 24 days, the animals were killed, the blood was collected for hematological and biochemical analysis, the organs were removed for histological analysis. After the storage, it could be observed that NCM stored in room temperature and 2 - 8 °C remained with their original particle size, zeta potential, polydispersity index and pH for 60 days. NCM stored at 40 °C, it could be observed a significantly increase in the particle size after 15 days, however zeta power and polydispersity index remained unchanged. The hematological analysis showed a significant increase (p<0.001) in total leukocytes in the groups white nanocapsules (BNCs) and NCM, and a significant decrease (p<0.01) in hemoglobin concentration and hematocrit in the group NCM after the intraperitoneal administrations. The biochemical analysis showed a significant increase (p<0.001) in the serum levels of urea and a significant decrease (p<0.001) in the serum levels of uric acid in the groups BNCs and NCM after the intraperitoneal administration. The histological analysis showed that only the group BNCs presented an inflammatory infiltrate of lymphocytes in the liver. It was also observed an inflammatory process in the abdominal cavity of the groups BNCs and NCM, after intraperitoneal administration. It was not observed significant changes in hematological, biochemical and histological analysis after the oral administration. In conclusion, the treatment of NCM for oral route did not cause toxicity according to the evaluated parameters and was considered safe for the use during 24 day period. However, the intraperitoneal route was not appropriate for administrating Eudragit nanocapsules.